Multi-grade fuzzy assessment framework for software professionals in work-from-home mode during and post-COVID-19 era - M. Suresh; Kavya Gopakumar (Future Business Journal, 2021)
The pandemic novel Coronavirus disease and the resulting lockdowns have contributed to major economic disturbances around the world, forcing organisations to extend the work-from-home (WFH) option to their employees wherever feasible. The current major challenge of this option is maintaining the efficiency and productivity of the employees across the organisations. It is therefore important to understand the impact of this make-shift arrangement of WFH policy and their underlying effects that may affect the efficiency of employees and hence their output levels. This is a distinctive approach to develop a unique framework for efficiency index computation by evaluating the efficiency levels of WFH mode in software organisations using multi-grade fuzzy approach and importance-performance analysis. In turn, this would help to determine the crucial attributes that require improvement to increase the efficiency levels of employees concerned. In this study, a case project has been assessed and it was observed that the efficiency index of WFH accounts to 4.92, which is in between the range of (4.01-6) specified as "Efficient". The framework can be used on a periodic basis to help software organisations to continuously improve their WFH efficiency level.
Keywords: 650; Importance-performance analysis; Multi-grade fuzzy; Online work during COVID-19; Software professionals; Work effectiveness; Work-from-home